Ultrahigh-compaction lithium iron phosphate positive electrode material as well as preparation method and application thereof
By designing the gradient temperature difference during the sintering process, the particle grading of lithium iron phosphate positive electrode material is achieved, which solves the problem of insufficient compaction density of lithium iron phosphate positive electrode material in the existing technology, and achieves ultra-high compaction density and performance improvement .
Patent Information
- Application Number
- CN202411435378.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to effectively increase the compaction density of lithium iron phosphate positive electrode material, resulting in insufficient energy density.
By designing the gradient temperature difference during the sintering process, the mixed powder grows into particles of different sizes at the gradient temperature, and grading of particles of different sizes is achieved, thereby improving the compaction density of lithium iron phosphate positive electrode material.
The ultra-high compaction density of lithium iron phosphate positive electrode material is achieved by greater than 2.7g/cm3, which improves its energy density and improves capacity, magnification and low-temperature performance.
Smart Images

Figure CN119409154A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion battery materials, and more specifically, to an ultrahigh-density lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are characterized by their lightness, high efficiency, long cycle life, and good safety performance, which have led to the continuous expansion of their application areas and their gradual application in the field of electric vehicles. At present, the mainstream positive electrode materials for lithium-ion batteries on the market are lithium iron phosphate positive electrode materials and ternary positive electrode materials. Lithium iron phosphate is highly valued for its high charge and discharge efficiency, good cycle stability, more durable batteries, high safety, low price, and abundant resources, and has been widely studied and applied; however, the energy density of lithium iron phosphate is still far behind that of ternary materials, and increasing the compaction density of lithium iron phosphate positive electrode materials can effectively increase the energy density of lithium iron phosphate batteries. There are many ways to increase the compaction density of lithium iron phosphate positive electrode materials. The mainstream is to achieve this through the grading of large and small particles, in which a moderate amount of large particles is the stacking skeleton, and a certain number of small particles fill the gaps to make the material stack more tightly, thereby increasing the compaction density; in addition, a moderate amount of small particles can improve the capacity, rate, and low-temperature performance of the material; the lithium iron phosphate positive electrode material finally prepared has both a high compaction density and good capacity, rate, and low-temperature performance.
[0003] At present, there are two ways to achieve the size particle grading more easily. The simplest way is to prepare large-particle finished products and small-particle finished products separately, and then directly blend the two finished products to achieve the size particle grading and obtain a high-density lithium iron phosphate positive electrode material; this method requires the preparation of two finished products separately, which is equivalent to requiring two independent sets of equipment, with complicated processes and large investment. Some also use two different iron phosphate mixtures and two different sand-grinding slurries to achieve the size particle grading and sintering to obtain a high-density lithium iron phosphate positive electrode material; this method also requires the mixing of two materials, which also has the disadvantages of complicated processes and large investment. Others add some specific additives to make some particles grow during the sintering process, while some particles are inhibited from growing, thereby achieving the size particle grading and obtaining a high-density lithium iron phosphate positive electrode material; however, this method is difficult to control the proportion of large and small particles, and it is impossible to determine how many particles can grow and how many particles can be inhibited from growing, so as to achieve a specific proportion of size particle grading. Its compaction density either does not meet the requirements, or its capacity, rate and low temperature performance are very poor after the compaction density meets the requirements.
[0004] The prior art discloses a method for preparing a high-density lithium iron phosphate positive electrode material, which first prepares a lithium iron phosphate precursor material with a large particle size and a lithium iron phosphate precursor material with a small particle size, and then calcines them at different temperatures respectively, and then mixes them to obtain a high-density lithium iron phosphate positive electrode material. However, the compaction density of the lithium iron phosphate positive electrode material prepared by the above method is generally still lower than 2.70g / cm 3 , its performance is still insufficient. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the primary purpose of the present invention is to provide a method for preparing an ultra-high-density lithium iron phosphate positive electrode material.
[0006] Another object of the present invention is to provide a lithium iron phosphate positive electrode material prepared by the above preparation method.
[0007] Another object of the present invention is to provide the use of the above-mentioned positive electrode material in the preparation of positive electrode plates for lithium-ion batteries.
[0008] Another object of the present invention is to provide a positive electrode plate for a lithium-ion battery.
[0009] Another object of the present invention is to provide the use of the above-mentioned lithium ion battery positive electrode sheet in the preparation of lithium ion batteries.
[0010] Another object of the present invention is to provide a lithium ion battery.
[0011] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0012] The present invention provides a method for preparing an ultra-high-density lithium iron phosphate positive electrode material, comprising the following steps:
[0013] The mixed powder of lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source is packed into a first container and a second container, and then sintered at high temperature simultaneously under an inert gas atmosphere to obtain the lithium iron phosphate positive electrode material after mixing;
[0014] During the high-temperature sintering process, the first container and the second container are placed in the same sintering container, the first container is placed on the second container, a first heat source is arranged above the first container, and a second heat source is arranged below the second container, the temperature of the first heat source is 720-760°C, and the temperature of the second heat source is 780-820°C; or, the temperature of the first heat source is 780-820°C, and the temperature of the second heat source is 720-760°C.
[0015] The present invention uses composite doping of multiple metal elements such as niobium, titanium, and tungsten. On the one hand, it can utilize the different effects of different doping elements on the growth of lithium iron phosphate particles to obtain lithium iron phosphate materials with better particle size and morphology; on the other hand, it can utilize the partial occupation of in-situ and non-in-situ lithium iron phosphate crystals by different doping elements, which can effectively improve the conductivity of the material.
[0016] Preferably, the Li / Fe molar ratio of the lithium source to iron phosphate is (1.0-1.1):1.
[0017] Preferably, the mass percentage of metallic niobium in the niobium-doped ferrophosphate to the iron element in the ferrophosphate is 0.02-0.04%.
[0018] Preferably, the mass percentage of the metallic titanium in the titanium source to the iron element in the ferric phosphate is 0.2-0.8%.
[0019] Preferably, the mass percentage of the metal tungsten in the tungsten source to the iron element in the ferric phosphate is 0.05-0.07%.
[0020] Preferably, the total amount of the composite carbon source accounts for 8.0-15.0% by mass of the ferric phosphate.
[0021] Preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium nitrate or lithium acetate.
[0022] Preferably, the composite carbon source comprises a first carbon source, a second carbon source and a third carbon source, the first carbon source is selected from at least one of glucose, starch, sucrose or phenolic resin, the second carbon source is selected from at least one of polyvinyl alcohol or polyethylene glycol, and the third carbon source is selected from at least one of graphene or carbon nanotubes.
[0023] More preferably, the mass ratio of the first carbon source, the second carbon source and the third carbon source in the composite carbon source is 60-80:20-38:0.5-2.
[0024] The present invention uses a precise amount of composite carbon source, which can effectively improve the conductivity of the material. At the same time, it can effectively utilize the different coating and conductivity of different carbon sources to produce different effects on the growth of material particles, effectively improving the compaction and electrical properties of the material.
[0025] Preferably, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, isopropyl titanate or tetraethyl titanate.
[0026] Preferably, the niobium in the niobium-doped ferrophosphate is derived from at least one of niobium pentoxide, niobium ethoxide or niobium chloride.
[0027] Preferably, the tungsten source is at least one of tungsten trioxide, metallic tungsten, tungsten chloride, sodium tungstate or tungsten sulfide.
[0028] More preferably, the D50 particle size of the mixed powder is 0.2-0.6 μm.
[0029] Preferably, the mixed powder of lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source is obtained by grinding and drying a mixed slurry of lithium source, niobium-doped iron phosphate, titanium source, tungsten source, composite carbon source and water.
[0030] More preferably, the weight of the water is 50% to 70% of the total weight of the slurry.
[0031] More preferably, the drying is spray drying.
[0032] Preferably, the sintering equipment is a double-layer roller kiln. More preferably, the sintering equipment is a double-layer multi-row roller kiln.
[0033] The present invention designs a gradient temperature difference during the sintering process, so that the mixed powder grows into particles of different sizes under the gradient temperature, realizes the gradation of large and small particles, and obtains ultra-high compacted lithium iron phosphate positive electrode materials. By adjusting the different temperature gradients of the upper and lower layers, the gradation of large and small particles with different proportions can be realized, thereby obtaining lithium iron phosphate positive electrode materials with different properties.
[0034] The present invention also provides a lithium iron phosphate positive electrode material prepared by the above preparation method.
[0035] The present invention also provides the use of the lithium iron phosphate positive electrode material in preparing a positive electrode sheet of a lithium ion battery.
[0036] The present invention also provides a lithium ion battery positive electrode plate, which contains the lithium iron phosphate positive electrode material.
[0037] The present invention also provides the use of the above-mentioned lithium ion battery positive electrode sheet in the preparation of lithium ion batteries
[0038] The present invention also provides a lithium ion battery, comprising the above-mentioned lithium ion battery positive electrode sheet.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The invention provides a method for preparing an ultra-high compacted lithium iron phosphate positive electrode material, wherein a gradient temperature difference is set in the same device, so that the mixed powder grows into particles of different sizes under the gradient temperature, and the size particle grading is achieved. The obtained lithium iron phosphate positive electrode material has a density greater than 2.7 g / cm 3 Ultra-high compaction density.
[0041] The present invention effectively improves the conductivity of the material by doping with multiple metal elements such as niobium, titanium, and tungsten and by different effects of different doping elements on the growth of lithium iron phosphate particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is an electron microscope image of the lithium iron phosphate positive electrode material of the upper sagger prepared in Example 1.
[0043] Figure 2 This is an electron microscope image of the lithium iron phosphate positive electrode material of the lower sagger prepared in Example 1.
[0044] Figure 3 This is an electron microscope image of the mixed lithium iron phosphate positive electrode material prepared in Example 1.
[0045] Figure 4 It is a schematic cross-sectional diagram of the double-layer multi-row roller kiln for charging and sintering used in the present invention, wherein: 1. upper layer heating element; 2. upper layer charging sagger; 3. lower layer charging sagger; 4. transmission rod; 5. lower layer heating element; 6. thermal insulation material around the kiln. DETAILED DESCRIPTION
[0046] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0047] The following examples and comparative examples all adopt Figure 2 The double-layer multi-row roller kiln shown is used for sintering. Figure 2 Middle: 1. Upper heating element; 2. Upper loading sagger; 3. Lower loading sagger; 4. Transmission rod; 5. Lower heating element; 6. Thermal insulation material around the kiln.
[0048] Example 1
[0049] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0050] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0051] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0052] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0053] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0054] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0055] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0056] Example 2
[0057] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0058] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0059] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0060] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0061] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0062] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 720°C for the upper heating element and 800°C for the lower heating element.
[0063] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0064] Example 3
[0065] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0066] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0067] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0068] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0069] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0070] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 720°C for the upper heating element and 820°C for the lower heating element.
[0071] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0072] Example 4
[0073] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0074] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0075] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0076] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron element in the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0077] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0078] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 780°C for the lower heating element.
[0079] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0080] Example 5
[0081] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0082] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0083] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0084] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0085] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0086] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 820°C for the lower heating element.
[0087] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0088] Example 6
[0089] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0090] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0091] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0092] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0093] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0094] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 760°C for the upper heating element and 780°C for the lower heating element.
[0095] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0096] Example 7
[0097] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0098] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0099] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0100] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0101] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0102] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 760°C for the upper heating element and 820°C for the lower heating element.
[0103] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0104] Comparative Example 1
[0105] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0106] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0107] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0108] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 70:29:1.
[0109] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0110] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 780°C for both the upper and lower heating elements.
[0111] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0112] Comparative Example 2
[0113] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0114] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0115] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0116] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.06% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.9% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.08% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 50:49:1.
[0117] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0118] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0119] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0120] Comparative Example 3
[0121] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0122] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0123] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0124] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 60% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.01% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.1% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.04% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of glucose, polyethylene glycol and graphene in the composite carbon source is 90:9:1.
[0125] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0126] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0127] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0128] Comparative Example 4
[0129] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0130] (1) adding a certain proportion of pure water, lithium source, iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0131] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; and the tungsten source is tungsten trioxide;
[0132] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic titanium in the titanium source to the iron element in the iron phosphate is 0.4%; the mass percentage of metallic tungsten in the tungsten source to the iron element in the iron phosphate is 0.06%; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0133] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0134] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0135] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0136] Comparative Example 5
[0137] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0138] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source and composite carbon source into a reaction kettle for stirring and dispersion;
[0139] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the Li / Fe molar ratio of the lithium source to the iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in the niobium-doped iron phosphate to the iron element in the iron phosphate is 0.03%; the mass percentage of metallic titanium in the titanium source to the iron element in the iron phosphate is 0.4%; the total amount of the composite carbon source to the iron phosphate is 10%, and the ratio of the composite carbon source is (70:29:1).
[0140] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0141] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0142] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0143] Comparative Example 6
[0144] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0145] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0146] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0147] The Li / Fe molar ratio of the lithium source to the iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in the niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the mass percentage of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0148] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0149] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0150] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0151] Comparative Example 7
[0152] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0153] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and carbon source into a reaction kettle for stirring and dispersion;
[0154] The lithium source is lithium carbonate; the carbon source is glucose; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; and the tungsten source is tungsten trioxide;
[0155] The Li / Fe molar ratio of the lithium source to the iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in the niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; and the total amount of carbon source is 10% of the iron phosphate.
[0156] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0157] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0158] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0159] Comparative Example 8
[0160] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0161] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and carbon source into a reaction kettle for stirring and dispersion;
[0162] The lithium source is lithium carbonate; the carbon source is polyethylene glycol; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; and the tungsten source is tungsten trioxide;
[0163] The Li / Fe molar ratio of the lithium source to the iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in the niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; and the total amount of carbon source is 10% of the iron phosphate.
[0164] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0165] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0166] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0167] Comparative Example 9
[0168] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0169] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and carbon source into a reaction kettle for stirring and dispersion;
[0170] The lithium source is lithium carbonate; the carbon source is graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; and the tungsten source is tungsten trioxide;
[0171] The Li / Fe molar ratio of the lithium source to the iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in the niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; and the total amount of carbon source is 10% of the iron phosphate.
[0172] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0173] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 800°C for the lower heating element.
[0174] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0175] Comparative Example 10
[0176] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0177] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0178] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0179] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0180] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0181] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 710°C for the upper heating element and 800°C for the lower heating element.
[0182] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0183] Comparative Example 11
[0184] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0185] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0186] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0187] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0188] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0189] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 770°C for the upper heating element and 800°C for the lower heating element.
[0190] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0191] Comparative Example 12
[0192] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0193] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0194] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0195] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0196] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0197] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 770°C for the lower heating element.
[0198] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0199] Comparative Example 13
[0200] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0201] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0202] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0203] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0204] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0205] (3) The powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for the upper heating element and 830°C for the lower heating element.
[0206] (4) The sintered materials are mixed and crushed to obtain an ultra-high-density lithium iron phosphate positive electrode material.
[0207] Comparative Example 14
[0208] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material comprises the following steps:
[0209] (1) adding a certain proportion of pure water, lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source into a reaction kettle for stirring and dispersion;
[0210] The lithium source is lithium carbonate; the composite carbon source is a composite of three carbon sources: glucose, polyethylene glycol and graphene; the titanium source is titanium dioxide; the niobium in the niobium-doped iron phosphate comes from niobium pentoxide; the tungsten source is tungsten trioxide;
[0211] The Li / Fe molar ratio of the lithium source to iron phosphate is 1.02:1; the weight of water is 40% of the total weight of the slurry; the mass percentage of metallic niobium in niobium-doped iron phosphate is 0.03% of the iron element in the iron phosphate; the mass percentage of metallic titanium in the titanium source is 0.4% of the iron element in the iron phosphate; the mass percentage of metallic tungsten in the tungsten source is 0.06% of the iron element in the iron phosphate; the total amount of the composite carbon source accounts for 10% of the iron phosphate, and the ratio of the composite carbon source is (70:29:1).
[0212] (2) The dispersed slurry is conveyed to a sand mill for grinding. After the grinding particle size D50 reaches 0.4 μm, the slurry is spray dried to obtain a dry powder.
[0213] (3) A portion of the powder is placed in the upper loading sagger and the lower loading sagger of a double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 740°C for both the upper heating element temperature and the lower heating element temperature.
[0214] (4) The other part of the powder is placed in the upper loading sagger and the lower loading sagger of the double-layer multi-row roller kiln and sintered in a nitrogen atmosphere for 8 hours. The sintering temperature is designed to be 800°C for both the upper heating element temperature and the lower heating element temperature.
[0215] (5) The materials obtained after sintering (3) and (4) are mixed and crushed to obtain an ultra-high-pressure compacted lithium iron phosphate positive electrode material.
[0216] Performance Testing
[0217] The lithium iron phosphate positive electrode materials obtained in the above examples and comparative examples were tested for their compaction density, and button batteries were made therefrom to test their electrical properties. The test results are as follows:
[0218] It can be seen from Table 1 that the compacted density of the lithium iron phosphate positive electrode materials prepared in all embodiments is 2.73-2.77 g / cm 3The 0.1C discharge specific capacity is between 163.7 and 164.4 mAh / g, and the 1C discharge specific capacity is between 148.6 and 151.7 mAh / g, and the compaction density and specific capacity are both good. For Example 1, the upper and lower layer temperatures are set the same, and both the compaction density and capacity deteriorate, among which the compaction density decreases more seriously. For Example 2 and Example 3, the mass percentage of metal niobium, the mass percentage of metal titanium, the mass percentage of metal tungsten and the proportion of the composite carbon source are not within the scope of the present invention, and both the compaction density and capacity deteriorate, among which the capacity decreases more seriously. For Example 4 to Example 6, the types of doped metals are reduced, and both the compaction density and capacity deteriorate, among which the capacity decreases more seriously. For Example 7 to Example 9, the types of carbon sources are reduced, and both the compaction density and capacity deteriorate. For Example 10 to Example 13, the upper or lower layer temperature exceeds the scope of the present invention, and the compaction density or capacity will deteriorate, and both the capacity and compaction density cannot be taken into account. In Comparative Example 14, the material is sintered twice at different temperatures, and then the materials sintered twice are mixed. The compaction density or capacity is worse than that of the embodiment, and the process is more complicated.
[0219] Table 1 Performance parameters of lithium iron phosphate positive electrode materials and button batteries prepared from each positive electrode material in each embodiment
[0220]
[0221]
[0222]
[0223] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-high-density lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: The mixed powder of lithium source, niobium-doped iron phosphate, titanium source, tungsten source and composite carbon source is packed into a first container and a second container, and then sintered at high temperature simultaneously under an inert gas atmosphere to obtain the lithium iron phosphate positive electrode material after mixing; During the high-temperature sintering process, the first container and the second container are placed in the same sintering container, the first container is placed on the second container, a first heat source is arranged above the first container, and a second heat source is arranged below the second container; The temperature of the first heat source is 720-760°C, and the temperature of the second heat source is 780-820°C; or, the temperature of the first heat source is 780-820°C, and the temperature of the second heat source is 720-760°C.
2. The preparation method according to claim 1, characterized in that: The composite carbon source comprises a first carbon source, a second carbon source and a third carbon source, wherein the first carbon source is selected from at least one of glucose, starch, sucrose or phenolic resin, the second carbon source is selected from at least one of polyvinyl alcohol or polyethylene glycol, and the third carbon source is selected from at least one of graphene or carbon nanotubes.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the first carbon source, the second carbon source and the third carbon source in the composite carbon source is 60-80:20-38:0.5-2.
4. The preparation method according to claim 1, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium nitrate or lithium acetate.
5. The preparation method according to claim 1, characterized in that: The titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, isopropyl titanate or tetraethyl titanate.
6. The lithium iron phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the lithium iron phosphate positive electrode material according to claim 6 in preparing positive electrode sheets for lithium-ion batteries.
8. A positive electrode plate for a lithium-ion battery, characterized in that: Contains the lithium iron phosphate positive electrode material as claimed in claim 6.
9. Use of the lithium ion battery positive electrode sheet according to claim 8 in the preparation of lithium ion batteries.
10. A lithium ion battery, characterized in that: A lithium-ion battery positive electrode sheet comprising the positive electrode sheet of claim 8.
Citation Information
Patent Citations
Lithium iron phosphate with high conductivity and high compaction density and preparation method thereof
CN113562712A
High-compaction-density lithium iron phosphate and preparation method thereof
CN113562714A
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN117691064A
Lithium iron phosphate positive electrode material and preparation method thereof, positive plate and lithium battery
CN118145616A
Cited By
Preparation method of lithium iron phosphate material
CN120246965A
Low-impurity phosphate positive electrode material and preparation method thereof, positive electrode and lithium secondary battery
CN120504306A
Preparation method and application of high-temperature-resistant lithium iron phosphate positive electrode material based on solid solution reaction
CN120757091A